Using ChatGPT for second language writing: Pitfalls and potentials - Barrot, Jessie S. (Assessing writing, 2023)
Recent advances in artificial intelligence have given rise to the use of chatbots as a viable tool for language learning. One such tool is ChatGPT, which engages users in natural and human-like interactive experiences. While ChatGPT has the potential to be an effective tutor and source of language input, some academics have expressed concerns about its impact on writing pedagogy and academic integrity. Thus, this tech review aims to explore the potential benefits and challenges of using ChatGPT for second language (L2) writing. This review concludes with some recommendations for L2 writing classroom practices. •ChatGPT is an AI-powered tool capable of generating human-like texts.•ChatGPT boasts affordances that may facilitate the teaching of writing.•ChatGPT has limitations in terms of accuracy and intelligibility of responses.•This paper recommends ways on how teachers can address challenges in using ChatGPT.